Pyrolysis characteristics, kinetics, thermodynamics and volatile products of waste medical surgical mask rope by thermogravimetry and online thermogravimetry-Fourier transform infrared-mass spectrometry analysis. (1st July 2021) - Chen, Ruiyu; Zhang, Deyuan; Xu, Xiaokang; Yuan, Yougen
Highlights: Pyrolysis of waste medical surgical mask rope is studied by TG-FTIR-MS. The thermal degradation process can be divided into two stages. The obtained kinetic parameters can well predict the thermal degradation behaviors. Volatile products and chemical reactions in the degradation process are determined. Abstract: Owing to the effects of Corona Virus Disease 2019 (COVID-19), numerous waste medical surgical mask ropes are generated. Pyrolysis is regarded as a promising method to dispose solid waste for energy and/or chemical feedstocks without pollution to the environment. In the present study, the pyrolysis characteristics, kinetics, thermodynamics and volatile products of waste medical surgical mask rope in inert atmosphere are studied and compared with those of typical polymers. The results indicate that the thermal degradation process of waste medical surgical mask rope may be divided into two stages with the threshold of α  = 0.05. Stage 1 (0 ≤  α  ≤ 0.05) and stage 2 (0.05 <  α  ≤ 1) are mainly resulted by the decomposition of spandex and nylon, respectively. Stage 2 may be nominally considered as a single-step reaction. The average activation energy, average pre-exponential factor and reaction model for stage 2 are 271.33 kJ/mol, 1.68 × 10 19 min −1 and g ( α )=(1- α ) -1 -1, respectively. These kinetic parameters can be used to well predict the thermal degradation behaviors in stage 2. Besides, the average activation energy of waste medical surgical mask rope under the present study is larger than that of nylon and spandex. In addition, the thermodynamic analysis indicates that the thermal degradation of waste medical surgical mask rope in inert atmosphere is favorable. The pyrolytic products mainly contain inorganic substances (ammonia, water, hydrogen cyanide, carbon monoxide, carbon dioxide), alkanes, alkynes, alkenes, aldehydes, amines, alcohols, carboxylic acids, ketones, aromatic compounds, nitriles, amide and its derivatives. The possible chemical reactions occurring in the thermal degradation process are suggested.